DEVELOPMENT OF MIXED MATRIX MEMBRANES FOR SEPARATION OF CO2 FROM CH4 - WIRYOATMOJO, AMELIA SUYONO WIRYOATMOJO (2010)
The rapid development in membrane technology for gas separation application to seek membrane with higher permeability and selectivity has motivated the present study to develop mixed matrix membranes. This is done by incorporating carbon molecular sieves (CMS) particles within polysulfone (PSU) matrix. The effect of CMS loading, annealing treatment and functionalization of CMS surface to the membrane morphology, mechanical, and viscoelastic properties were evaluated. The performance of fabricated membranes was evaluated in term of permeability and selectivity of CO2 and CH4. Morphology analysis found that CMS and PSU have a good adhesion. It was also found that the introduction of CMS led to the formation of restricted mobility polymer regions surrounded CMS particles, indicated by the appearance of dual glass transition temperature (Tg). Adhesion of PSU-CMS within the membranes was explained using the profile of tan δ and storage modulus, and the stress-strain curve. Membranes with annealing treatment have shown better adhesion between the two phases indicated by the reduction of tan δ peaks area with the shifting of the second Tg to a lower temperature, higher storage modulus, and the occurrence of necking process. It was also found that functionalization of CMS surface by nitric acid oxidation further enhanced PSU-CMS adhesion. The formation of functional groups on CMS surface was confirmed by FTIR spectra and the reduction of its intermolecular distance. Permeability of CO2 and CH4 indicated that the mixed matrix membrane has high ideal selectivity of CO2/CH4 compare to PSU membrane. Within the pressure range of CO2 from 2 to 10 bar, the addition of 30 wt.% of CMS has increased the permeability of CO2 and the ideal selectivity of CO2/CH4 up to 7-37% and 132-344%, respectively. However annealing treatment decreased the permeability of CO2 as much as 12-29%, but increased its ideal selectivity as much as 165-823%. Similarly by using surface vii functionalized CMS, the permeability of CO2 was decreased as much as 2-5% and increased its ideal selectivity as much as 183-516%. Mixed matrix membranes modified by annealing treatment and employing surface functionalized CMS had successfully surpassed the upper-bound trade-off limit of polymeric membranes.